Moving on to Not Fall Behind? Artificial Intelligence (AI) and Small and Medium-Sized Enterprises (SMEs) Performance - Mohd Noor, Nurul Hidayana; Fuzi, Amirah Mohamad; Mohamad Fadzil, Nurin Farzana; El Ashfahany, Afief (Journal of Techno-Social, 2025)
Artificial Intelligence (AI) is not just a futuristic dream but a game changer for business. From improving customer experience to streamlining operations and unlocking new growth opportunities, AI is profoundly changing business. By embracing AI, businesses can gain a competitive advantage, improve customer experience, improve decision-making, and drive innovation. This study examines the impact of AI readiness, government support for AI, and business innovation on SME performance. The second is to examine the indirect path of business innovation on the proposed relationship. The study employed a cross-sectional survey of the population of young entrepreneurs in Negeri Sembilan, Malaysia. The sample involves 384 respondents who were purposively selected. The data were analyzed using Structural Equation Modeling (SEM). The findings have discovered that AI readiness, government support, and business innovation influence SME performance. Moreover, business innovation has a strategic impact on the growth and success of the SMEs. It acts as a mediator to strengthen the impact of AI readiness and government support for AI on business performance. This study aims to help SMEs make the most of the potential of AI tools to improve their business strategies and compete in an increasingly challenging digital market. In addition, innovation is the foundation for sustainable growth, intense competitiveness, and adaptation to the inevitable change that needs to be utilized by all entrepreneurs.